Targeting ferroptosis regulators by natural products in colorectal cancer - Zhang, Yiping; Xie, Jun (Frontiers in Pharmacology, 2024)
Colorectal cancer (CRC) poses a significant global health challenge, ranking as the third most diagnosed cancer and the second leading cause of cancer-related deaths. Despite advancements in treatment, challenges such as delayed diagnosis, multidrug resistance, and limited therapeutic effectiveness persist, emphasizing the need for innovative approaches. This review explores the potential of natural products, nutraceuticals, and phytochemicals for targeting ferroptosis-related regulators as a novel strategy in CRC. Ferroptosis, a form of regulated cell death characterized by iron-dependent lethal lipid peroxide accumulation, holds substantial importance in CRC progression and therapy resistance. Natural products, known for their diverse bioactive effects and favorable safety profiles, emerge as promising candidates to induce ferroptosis in CRC cells. Exploring amino acid, iron, lipid metabolism regulators, and oxidative stress regulators reveals promising avenues for inducing cell death in CRC. This comprehensive review provides insights into the multifaceted effects of natural products on proteins integral to ferroptosis regulation, including GPX4, SLC7A11, ACSL4, NCOA4, and HO-1. By elucidating the intricate mechanisms through which natural products modulate these proteins, this review lays the foundation for a promising therapeutic strategy in CRC.